By the shores of Silver Lake - Wilder, Laura Ingalls; Williams, Garth (New York : HarperTrophy, 1971)
The Ingalls family moves to the Dakota territory, claims a homestead, and braves the hardships and perils of living on the frontier.
Booklist.
Library Journal.
Newbery Medal/Honor.
Booklist, May 1998.
Horn Book, April 1998.
Library Journal, June 2001.
Keywords: Frontier and pioneer life -- Fiction; Historical fiction; Frontier and pioneer life -- Fiction; Historical fiction